Gestão logística: com enfoque em gerenciamento de estoques e distibuição física em uma agencia bancária - (:unkn) unknown (Universidade Federal do Pampa, 2014)
In the search for better results and methods of adequate managerial administration, the organizations can take advantage of the existence of diversified knowledge, that approach in different ways the problematic of nowadays managerial reality. This paper had as study environment a bank agency, located in the city of Bagé (RS), which has in the administrative support section some operational characteristics that might be related to the logistic concepts, as we are dealing with company that provides service. These concepts were divided two big logistic areas: Material Administration and Physical Distribution. In each of the main aspects that could influence in their operations, better organization, control, handling and movement of materials with different individual characteristics and their respective flows of information. As the aim of this paper, a survey was conducted about the necessary information to identify the types of stocks, the existence of logistic management for further proposal of logistics management in materials with a focus on inventory management and physical distribution. For data collection, an observation was realized about the environment and the items that need research, for further descriptive register, supported by structured interviews with those who participate in activities that involve sectors of the company that the case study was developed. This information was used to, according to the theoretical framework, seek appropriate logistics solutions to the shortcomings and difficulties found, so it is proposed a management model for the administrative support sector in this bank agency.
Keywords: Engenharia; Engenharia da produção; Agência Bancária; Serviços; Logística; Administração da produção; Administração de materiais; Distribuição física; Engineering; Production engineering; Banking agency; Services; Logistics; Production management; Materials management; Physical distribution; CNPQ::ENGENHARIAS